Novel Carbonyl Analogs of Tamoxifen: Design, Synthesis, and Biological Evaluation - Kasiotis, Konstantinos M.; Lambrinidis, George; Fokialakis, Nikolas; Tzanetou, Evangelia N.; Mikros, Emmanuel; Haroutounian, Serkos A. (Frontiers in Chemistry, 2017)
Aim of this work was to provide tamoxifen analogues with enhanced estrogen receptor binding affinity. Hence, several derivatives were prepared using an efficient triarylethylenes synthetic protocol. The novel compounds bioactivity was evaluated through the determination of their receptor binding affinity and their agonist/antagonist activity against breast cancer tissue using a MCF-7 cell-based assay. Phenyl esters 6a,b and 8a,b exhibited binding affinity to both ERα and ERβ higher than 4-hydroxytamoxifen while compounds 13 and 14 have shown cellular antiestrogenic activity similar to 4-hydroxytamoxifen and the known estrogen receptor inhibitor ICI182,780. Theoretical calculations and molecular modelling were applied to investigate, support and explain the biological profile of the new compounds. The relevant data indicated an agreement between calculations and demonstrated biological activity allowing to extract useful structure-activity relationships. Results herein underline that modifications of tamoxifen structure still provide molecules with substantial activity, as portrayed in the inhibition of MCF-7 cells proliferation.